2023
DOI: 10.1007/s40279-022-01804-x
|View full text |Cite
|
Sign up to set email alerts
|

Resistance Training Induces Improvements in Range of Motion: A Systematic Review and Meta-Analysis

Abstract: Background Although it is known that resistance training can be as effective as stretch training to increase joint range of motion, to date no comprehensive meta-analysis has investigated the effects of resistance training on range of motion with all its potential affecting variables. Objective The objective of this systematic review with meta-analysis was to evaluate the effect of chronic resistance training on range of motion compared either to a contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 101 publications
0
19
2
Order By: Relevance
“…Given the broadness of these responses and the varied nature of injuries sustained in judo, it may infer that there is no common consensus on the most appropriate exercises to reduce injuries and that a more general or individualized approach to injury reduction may be favored. Approximately two-thirds of participants in this study did not believe that S&C was very important for the development of flexibility, which is contrary to current research, which suggests resistance exercises may improve flexibility and range of motion to similar effects as static stretching (2,51). This may indicate that research on specific topics regarding the benefits of S&C for physical performance in judoka could be more effectively educated and disseminated.…”
Section: Discussioncontrasting
confidence: 99%
“…Given the broadness of these responses and the varied nature of injuries sustained in judo, it may infer that there is no common consensus on the most appropriate exercises to reduce injuries and that a more general or individualized approach to injury reduction may be favored. Approximately two-thirds of participants in this study did not believe that S&C was very important for the development of flexibility, which is contrary to current research, which suggests resistance exercises may improve flexibility and range of motion to similar effects as static stretching (2,51). This may indicate that research on specific topics regarding the benefits of S&C for physical performance in judoka could be more effectively educated and disseminated.…”
Section: Discussioncontrasting
confidence: 99%
“…However, to increase the ROM in the long-term even other strategies than stretching were reported to increase the ROM to a similar extent. Alizadeh et al (2023) for example, showed in their metaanalysis that frequent resistance training performed within the full ROM can chronically increase the ROM of a joint. Besides the increase in ROM, resistance training has certainly other beneficial effects such as for example, increase in muscle strength and muscle mass, reducing back pain, and enhancing cardiovascular health (Westcott, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…However, it has to be mentioned at this point that techniques other than static stretching or foam rolling can increase the ROM of a joint in the long term. Alizadeh et al [8] showed in their meta-analysis that frequent resistance training performed within the full ROM can increase joint ROM long term. In addition to the increase in ROM, resistance training has other beneficial effects such as increases in muscle strength and mass, reducing back pain, and enhancing cardiovascular health [29].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to stretch training, other strategies such as resistance training, when performed through the whole ROM [8], or foam rolling [9] can also increase joint ROM long term. According to previous meta-analyses, long-term stretch training and resistance training can be considered similarly effective for increasing the ROM (effect size [ES] = 0.08; p = 0.79) [8,10].…”
Section: Introductionmentioning
confidence: 99%